2013
DOI: 10.1371/journal.pone.0078505
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal and Non-Exosomal Transport of Extra-Cellular microRNAs in Follicular Fluid: Implications for Bovine Oocyte Developmental Competence

Abstract: Cell-cell communication within the follicle involves many signaling molecules, and this process may be mediated by secretion and uptake of exosomes that contain several bioactive molecules including extra-cellular miRNAs. Follicular fluid and cells from individual follicles of cattle were grouped based on Brilliant Cresyl Blue (BCB) staining of the corresponding oocytes. Both Exoquick precipitation and differential ultracentrifugation were used to separate the exosome and non-exosomal fraction of follicular fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
273
1
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(305 citation statements)
references
References 63 publications
15
273
1
10
Order By: Relevance
“…With a few exceptions (Carletti et al 2010, Kitahara et al 2013, most evidence on follicular roles of miRNAs has been obtained using cultured cells, particularly rodent cells, and in some cases actual changes in the expression of these miRNAs during follicle development have not been demonstrated. Indeed, although genome-wide miRNA analyses of whole ovarian tissues (Landgraf et al 2007, Ro et al 2007, Mishima et al 2008, Hossain et al 2009, Ahn et al 2010, Juanchich et al 2013 or follicular, or luteal tissues (Fiedler et al 2008, McBride et al 2012, Miles et al 2012, da Silveira et al 2012, Donadeu & Schauer 2013, Schauer et al 2013, Sohel et al 2013 have been reported in several species, detailed spatiotemporal profiles encompassing several follicle developmental stages have not. Identifying such profiles will be an important step toward understanding the functional involvement of miRNAs during specific stages of follicle development.…”
Section: Introductionmentioning
confidence: 99%
“…With a few exceptions (Carletti et al 2010, Kitahara et al 2013, most evidence on follicular roles of miRNAs has been obtained using cultured cells, particularly rodent cells, and in some cases actual changes in the expression of these miRNAs during follicle development have not been demonstrated. Indeed, although genome-wide miRNA analyses of whole ovarian tissues (Landgraf et al 2007, Ro et al 2007, Mishima et al 2008, Hossain et al 2009, Ahn et al 2010, Juanchich et al 2013 or follicular, or luteal tissues (Fiedler et al 2008, McBride et al 2012, Miles et al 2012, da Silveira et al 2012, Donadeu & Schauer 2013, Schauer et al 2013, Sohel et al 2013 have been reported in several species, detailed spatiotemporal profiles encompassing several follicle developmental stages have not. Identifying such profiles will be an important step toward understanding the functional involvement of miRNAs during specific stages of follicle development.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of EVs containing microRNAs has been described in equine, bovine and human ovarian follicular fluid (da Silveira et al 2012, Sang et al 2013, Sohel et al 2013, Santonocito et al 2014, Navakanitworakul et al 2016. Using transmission electron microscopy and flow cytometry, da Silveira and coworkers reported the presence of a heterogenous sized population of EVs in equine follicular fluid (da Silveira et al 2012).…”
Section: Presence Of Evs Containing Micrornas In Follicular Fluidmentioning
confidence: 99%
“…Sohel and coworkers isolated EVs from follicular fluid of growing and fully grown bovine follicles (Sohel et al 2013). PCR array analysis of 748 known microRNAs uncovered 509 microRNAs present in follicular fluid EVs, with 40 microRNAs that are present at different levels between growing and fully grown follicles, suggesting a role for these EV microRNAs in follicular growth.…”
Section: Presence Of Evs Containing Micrornas In Follicular Fluidmentioning
confidence: 99%
“…They are found in the diverse compartments of ovarian follicles, including granulosa cells (Hatzirodos et al, 2014a), theca cells (Hatzidoros et al, 2014b), follicular fluid and oocytes (Bonnet et al, 2008). Studies demonstrated their role in follicle development of humans (Sirotkin et al, 2009;Sang et al, 2013;Roth et al, 2014), mice (Fiedler et al, 2008;Carletti et al, 2010), cattle (Tesfaye et al, 2009;Ma et al, 2011;Sohel et al, 2013), pigs (Lin et al, 2012;Donadeu and Schauer, 2013) and horses (Da Silveira et al, 2012). Data suggest that miRNAs may regulate cellular differentiation during follicular development and may contribute to the oocyte-somatic cells dialog during the acquisition of oocyte developmental competence.…”
Section: Introductionmentioning
confidence: 99%
“…In cattle, miRNAs were found in follicular fluid and their profile changes during folliculogenesis (Zielak-Steciwko et al, 2014). They are both free and associated with exosomes; the latter possibly facilitating the transport of specific miRNAs into follicular cells (Sohel et al, 2013). This review will attempt to summarize the current knowledge on mRNAs and miRNAs associated with a correct folliculogenesis and oogenesis processes.…”
Section: Introductionmentioning
confidence: 99%